Role of gene Xpert test in clinical TB suspect in children - Gupta, Sheenu; Kotrashetti, Veerana; Ahmed, Rizwan (International Journal of Contemporary Pediatrics, 2018)
Background: Tuberculosis (TB) is a major global health problem. Childhood tuberculosis (TB) is common in our community but it is relatively neglected, due to greater challenges in diagnosis. Clinical manifestations of childhood TB differ from adults. The diagnosis in most cases is based on clinical evidence but chest X-ray, Mantoux test, history of Kochs contact, malnutrition and sputum/gastric sample microscopy are important supporting investigations. WHO recommended use of newer diagnostic tests like Gene Xpert in pediatric cases where TB is mostly paucibacillary and identification of TB bacilli is difficult for confirmation of diagnosis. Methods: This prospective study was conducted among admitted and OPD patients in the department of Pediatrics over a period of 1and half year. Clinically suspected cases of TB in the age group 0-12 years who met the diagnostic criteria made the study group. Refusal of consent by parent and children already on TB treatment were excluded from this study. Investigations like chest X-ray, Mantoux test, sputum/gastric aspirate microscopy and Gene Expert were done to confirm the clinical diagnosis. Results: Pulmonary tuberculosis was more common (28%), TB lymphadenitis 22%, TB meningitis 14%, Tubercular Pleural effusion 12 %. and rest were no TB. BCG scar was present in 90%. History of contact was present in 76% and Mantoux test was positive in 76%. Gene Expert was positive only in one case in our study rest 49 cases were negative. The most common symptoms were fever (72%), cough (52%) and weight loss (40%). Conclusions: This study supports that detailed history, clinical evaluation and active investigative workup in addition to newer diagnostic tests like Gene Xpert has a major role in diagnosing childhood tuberculosis.